Efficacy of Montelukast as Added Therapy in Patients with Chronic Idiopathic Urticaria - Khan, Sujoy; Lynch, Nuala (Inflammation & Allergy-Drug Targets (Discontinued), 2012)
Chronic idiopathic urticaria is a common skin disorder characterized by recurrent appearance of wheals and/or angioedema for more than 6 weeks without an identifiable cause. Consensus guidelines suggest use of leukotriene receptor antagonists (montelukast or zafirlukast) in patients whose urticaria is resistant to antihistamines. Our objectives were (1) document the efficacy of montelukast in our patients, and (2) evaluate whether any clinical features or available laboratory investigations were associated with a response to montelukast. Patients who received montelukast between the years 2008-2011 (4-year period) were retrospectively identified from clinic letters. Clinical features and laboratory investigations were collected and analyzed. The primary end point was adequate control of disease without the need for systemic steroid therapy. 25 patients (10 males and 15 females; median age, 33 years; age range, 13-66 years) with an average duration of urticaria at 3.8 years received montelukast 10mg daily. 12 patients (48%) were better on montelukast with combined anti-H1 and anti-H2 therapy, with no statistical significance between median age and duration of urticaria between males and females. In 11 patients, montelukast had no effect and in 2 patients the urticaria worsened after montelukast was started. 15 patients had peripheral blood basopenia of which 5 patients responded to montelukast. Two patients had positive antinuclear antibody, 3 thyroid peroxidase antibodies and 4 with positive basophil histamine release. All 20 patients who had complement C3 and C4 levels done were within normal limits. Four of 6 patients (67%) with positive specific IgE responded to montelukast and combined anti-H1/H2 therapy. Almost half of our patients with chronic urticaria responded to montelukast and combined anti-H1 and anti-H2 therapy. We were unable to identify any clinical features or laboratory markers that were associated with a response to montelukast. Further studies are required to understand the failure of response of leukotriene inhibition in urticaria.
Keywords: montelukast